PFM as a tool for sustainable development: Lessons from Southwest Ethiopia - Tesfaye, Getachew; Ayele, Kalkidan; Tamene, Lulseged (2024)
Participatory Forest Management (PFM) is known as to play a vital role in conserving forests and biodiversity while simultaneously generating sustainable livelihoods by empowering local communities to actively manage forest resources. PFM in Southwest Ethiopia has demonstrated positive impacts on biodiversity, livelihoods, and property rights. Grassroots forest management groups like forest management associations and cooperatives, play a crucial role. While local communities are largely engaged, women’s participation remains limited. Key challenges include equitable benefits-sharing, insufficient government support, and financial sustainability. To ensure long-term success, PFM initiatives need stronger institutional support, improved market access, and gender sensitive approaches.